2021
DOI: 10.1186/s12944-021-01586-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between genetic polymorphism of drug transporters and the efficacy of Rosuvastatin, atorvastatin and simvastatin in patients with hyperlipidemia

Abstract: Background To determine the effect of genetic polymorphism of drug transporters on the efficacy of treatment with Rosuvastatin, Atorvastatin and Simvastatin in patients with hyperlipidemia. Methods The study consists of 180 patients, aged 40–75 years, with hyperlipidemia. All patients were divided into two equal groups: patients with different SLCO1B1 (521CC, 521CT and 521TT) and MDR1 (3435CC, 3435TC and 3435TT) genotypes. Each group was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…It is well-studied that genetic variation of c.521T > C in SLCO1B1 is a genetic risk factor for statin myopathy ( 39 ). Sivkov et al found that statin therapy was less effective in SLCO1B1 c. 521CC genotype carriers ( 40 ), who considered TC and LDL-C reduction as the efficacy of statins. However, a meta-analysis of 8 studies, including 2012 wild genotype (T/T) patients and 526 variant genotype (T/C and C/C) cases, found no significant association between the lipid-lowering efficacy of statins and the SLCO1B1 c.521T > C polymorphism ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-studied that genetic variation of c.521T > C in SLCO1B1 is a genetic risk factor for statin myopathy ( 39 ). Sivkov et al found that statin therapy was less effective in SLCO1B1 c. 521CC genotype carriers ( 40 ), who considered TC and LDL-C reduction as the efficacy of statins. However, a meta-analysis of 8 studies, including 2012 wild genotype (T/T) patients and 526 variant genotype (T/C and C/C) cases, found no significant association between the lipid-lowering efficacy of statins and the SLCO1B1 c.521T > C polymorphism ( 41 ).…”
Section: Discussionmentioning
confidence: 99%